ANÁLISE DO DESEMPENHO TÉRMICO EM HABITAÇÃO UNIFAMILIAR DE INTERESSE SOCIAL EM CURITIBA - Santos, Jéssica Mara; Freitas, Ludmylla Faria de; Oliveira, Raquel Diniz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In Brazil, dwelling programs adopt standardized building solutions, disregarding the climatic singularity of each region of the country. The objective proposed for this paper was the building envelope thermal performance evaluation of a single family social housing located in Curitiba, Brazil. The building evaluation was carried out through two methods: simplified and computational simulation, according to parameters established by NBR 15,575 (2013). The simplified method results indicated noncompliance with the standard criterion of thermal transmittance for the external walls of the case study. Through Design Builder® simulation, it was verified that the building complies with the standard criteria for a typical summer and winter day in Curitiba, Brazil. In sum, It was observed that an insulation improvement could enhance the human thermal comfort conditions for the case study in Curitiba, Brazil. On the other hand, the building simulation method established in NBR 15.575 was not enough to define a thermal performance level tied to human thermal comfort conditions. In addition, the thermal comfort further analysis proved to be relevant to quantify the thermal comfort hours provided by the different construction systems as well as to foster the building thermal performance analysis.